KARAKTERISTIK SIFAT KIMIA TANAH RIZOSFER SELEDRI PADA SISTEM MONOKULTUR DI SENTRA PRODUKSI SAYURAN BANJARBARU, KALIMANTAN SELATAN - Muhammad, Rizki; Saidy, Akhmad Rizalli; Ichriani, Gusti Irya; Yusriadi, Yusriadi (Universitas Lambung Mangkurat, 2026)
Celery (Apium graveolens L.) is an important horticultural crop widely cultivated and consumed in Indonesia, particularly leaf celery, which is valued for culinary use and traditional medicinal properties. High market demand has driven intensive celery cultivation under a monoculture system in vegetable production centers such as Landasan Ulin Utara, Banjarbaru, South Kalimantan. Long-term monoculture practices are known to potentially degrade soil quality and increase plant susceptibility to diseases, yet information on the chemical characteristics of celery rhizosphere soil in this region remains limited. This study aimed to evaluate the chemical properties of celery rhizosphere soil under a monoculture system at three cultivation sites in Banjarbaru. Soil sampling was conducted from August to November 2025, and analyses included soil pH, organic carbon, total nitrogen, C/N ratio, available phosphorus, and exchangeable base cations (K, Ca, Na, and Mg) using standard laboratory methods. The results showed that soil chemical properties were relatively homogeneous across locations and between symptomatic and asymptomatic plants affected by root-knot disease. Overall, the soils exhibited neutral pH, high organic carbon, moderate total nitrogen, high available phosphorus, and relatively unbalanced base cation composition. These findings indicate that root-knot disease occurrence is not directly associated with soil chemical variability but is likely influenced by biological factors in the rhizosphere. The results provide baseline edaphic data to support sustainable soil management and further research on soil biology and disease control in celery cultivation.